Chiara Cappelletto, Neuroestetica. L'arte del cervello. (Altre Modernità, 2010)
Chiara Cappelletto, Neuroestetica.L'arte del cervello.(Roma-Bari, Laterza, 2009, pp. 203, ISBN - 9788842088998)di Elio Franzini